2020
DOI: 10.1016/j.amj.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Interhospital Transfer of Critically Ill Patients Because of Coronavirus Disease 19–Related Respiratory Failure

Abstract: Highlights Given the prevalence and severity of illness associated with coronavirus disease 2019 (COVID-19)–related acute respiratory failure, it is very likely that community hospitals will need to transfer such patients to regional centers capable of providing advanced care, such as extracorporeal membrane oxygenation support. The critical care transport team must be familiar with transporting these patients in the prone position because this position has been shown to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 9 publications
3
39
0
10
Order By: Relevance
“…Transport teams were all composed of at least one EP and one emergency nurse for each patient, and another physician was present as a team leader to coordinate the transport, but also as a referent in case of adverse event or need. However, a previous study showed that short air transport (25 min) for COVID-19 patients can be safe and feasible [22,23].…”
Section: The Necessity To Help Overcrowded Areasmentioning
confidence: 98%
“…Transport teams were all composed of at least one EP and one emergency nurse for each patient, and another physician was present as a team leader to coordinate the transport, but also as a referent in case of adverse event or need. However, a previous study showed that short air transport (25 min) for COVID-19 patients can be safe and feasible [22,23].…”
Section: The Necessity To Help Overcrowded Areasmentioning
confidence: 98%
“…It is common for the patients to experience adverse events during transport, even the shortest transport may cause life-threatening conditions [ 7 , 9 – 11 ]. Patient transport can lead to various adverse events such as severe hypotension, decreasing level of consciousness, oxygen desaturation, accidental extubation, poorly or incorrectly placed endotracheal tube, procedural errors, neurological deterioration, medication errors, accidental physical injuries, longer hospital, and intensive care unit (ICU) stay, and death [ 7 , 10 , 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Civilian transport services made similar efforts to augment critical care and infection isolation capabilities for interfacility transports of critically ill patients with COVID-19. 7,8 The aim of this study was to describe characteristics and in-flight interventions for patients with COVID-19 requiring aeromedical evacuation by CCATT. Describing critically ill patients with COVID-19 and resources utilized for aeromedical evacuation will help inform planning and delivery of future en route care for COVID-19 and other highly contagious diseases.…”
Section: Introductionmentioning
confidence: 99%